Pendidikan Karakter Dalam Al-Quran - Suharmoko Suharmoko (Al-Riwayah : Jurnal Kependidikan, 2016)
ducation is a process of change or personal development of the students in all aspects of life, forming a complete personality (Insan Kamil) either as social beings, as well as individual beings, so that they can adapt and live in the wider community well, including being responsible to yourself, others, and God. Character education is a system of cultivation of character values that include components of knowledge, awareness or willpower, and actions to implement these values, either against God, ourselves, and others, the environment. When character education is applied systematically and sustainably, a child will be better in emotional management. This emotional intelligence is an important provision in preparing children to meet the future, because someone more easily and successfully to face all kinds of life challenges, including the challenge to succeed academically. This paper elaborates character education in the perspective of the Quran as a holy book of Muslims.